Indonesian High School Students’ Readiness and Attitude toward Online Learning: A Mixed Method Study - Bachtiar Bachtiar (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aims to find out students’ readiness and attitude of online learning and how their learning readiness and attitude affect their participation and academic achievement in online learning. This research used A Mixed Method Research (MMR) by distributing questionnaires and conducting a depth interviews.  The questionnaire were distributed to 50 students in 5 senior high schools in one district in South  Sulawesi province of Indonesia, and 5 of the students who responded the questionnaire were selected to be interviewed. The quantitative data from the questionnaire was analyzed using the Statistical Package for Social Sciences (SPSS), while the qualitative data from the interview was analyzed using thematic analysis. The results showed that students’ readiness and attitude have been found to impact students’ level of involvement in English online learning. Some factors influenced the students’ readiness, namely: lack of technological understanding in relation to digital learning platform, technological devices for virtual learning, quotas, and internet access. The study also found that, despite the students negative attitude toward online learning at the beginning of the implementation of online learning, they have learnt new somethings in relation to education technology which influenced their positive attitude towards online learning, including English online learning. The study suggests the need for teachers to implement effective learning approach and strategy to enhance students involvement in online learning